2012
DOI: 10.1002/ejic.201200510
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Anchoring on Magnetic Fe3O4 Nanoparticles Modified with Phosphonic Linkers

Abstract: Magnetic Fe 3 O 4 nanoparticles (MNPs) have been covalently modified with β-cyclodextrin (β-CD) cavities by adopting a two-step anchoring route based on particle prefunctionalization with a phosphonic monolayer, which acts as a covalent linker between the MNPs and β-CD. Particular attention has been devoted to the study of the functionalization process by adopting bifunctional phosphonic linkers to investigate the efficiency of the anchoring group (phosphonic acid or ester)[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…Mutin et al [114] reported the selective surface modification by phosphonic acids of SiO 2 -TiO 2 . Tudisco et al [115] modified the Fe 3 O 4 NPs with phosphonic acids and then covalently functionalized with ␤-CD (Fig. 22).…”
Section: Organophosphorusmentioning
confidence: 99%
“…Mutin et al [114] reported the selective surface modification by phosphonic acids of SiO 2 -TiO 2 . Tudisco et al [115] modified the Fe 3 O 4 NPs with phosphonic acids and then covalently functionalized with ␤-CD (Fig. 22).…”
Section: Organophosphorusmentioning
confidence: 99%
“…[20] reported a chitosan crosslinked carboxymethyl-β-cyclodextrin polymer modified Fe 3 O 4 A c c e p t e d M a n u s c r i p t 3 magnetic nanoparticles for delivering hydrophobic 5-fluorouracil. Other carriers of β-CD modified Fe 3 O 4 for delivery of diclofenac sodium salt, [21] tamoxifen, [22] camptothecin, [23] curcumin [24] and so on, have been reported. Abundant research efforts have been made in constructing MNPs-β-CD nanohybrids for drug delivery.…”
Section: Introductionmentioning
confidence: 98%
“…40 Moreover, PHA molecules have aliphatic chains, the adsorption energy of which can be responsible for the decrease in the diameter of Fe 3 O 4 -PHA NPs as reported in the case of the use of ammonium base (R 4 NOH with R = CH 3 , C 2 H 5 , C 3 H 7 ) during iron oxide NP synthesis. 42,43 Measurements by XPS presented in Fig. The presence of phosphorus, carbon and oxygen elements which compose PHA is confirmed in Fig.…”
Section: Papermentioning
confidence: 67%